A multicase study to understand how singularity is taken into account in a co-evaluation of a teaching traineeship situation - Maes, Olivier; Colognesi, Stéphane; Van Nieuwenhoven, Catherine (Swiss Journal of Educational Research, 2019)
In the context of initial teacher training in the French speaking part of Belgium, supervisors are required to evaluate trainees, in particular through co-evaluations. In this context, this contribution aims to answer the following question: How is the singularity of the situation taken into account in the construction of the supervisor’s evaluative judgment? To answer this question, we conducted a multi-case study built around eight co-evaluation interviews. The results highlight that the supervisors of the study take into account the internship context and / or the personal aspects of the student to build their evaluative judgment.